2023
DOI: 10.1038/s41598-023-33372-z
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study on diabetic cutaneous wound healing with radiation crosslinked bilayer collagen scaffold in rat model

Abstract: Diabetes may leave patients more prone to skin problems, and minor skin conditions can more easily turn into serious damage to the extracellular matrix, which further impairs the skin's mechanical properties and delays wound healing. Therefore, the aim of the work is to develop extracellular matrix substitution to remodel the mechanical properties of diabetic cutaneous wound and thus accelerate diabetic wound healing. A green fabrication approach was used to prepare radiation crosslinked bilayer collagen scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Collagen and chitosan-based sponges are the most commonly used scaffolds for MSC delivery[ 200 ]. As for the usage of SLS in diabetic wound treatment, collagen scaffold derived from bovine skin has been shown to result in improved biocompatibility, re-epithelization, anti-inflammatory effects, and neovascularization of chronic wounds in diabetic mice[ 215 , 216 ]. Studies performed on MSCs and exosomes have further showed that the combination of gingival MSC-derived exosomes and hydrogel sponges accelerates skin wound healing and the re-epithelization process[ 217 ].…”
Section: Diabetes Comorbiditiesmentioning
confidence: 99%
“…Collagen and chitosan-based sponges are the most commonly used scaffolds for MSC delivery[ 200 ]. As for the usage of SLS in diabetic wound treatment, collagen scaffold derived from bovine skin has been shown to result in improved biocompatibility, re-epithelization, anti-inflammatory effects, and neovascularization of chronic wounds in diabetic mice[ 215 , 216 ]. Studies performed on MSCs and exosomes have further showed that the combination of gingival MSC-derived exosomes and hydrogel sponges accelerates skin wound healing and the re-epithelization process[ 217 ].…”
Section: Diabetes Comorbiditiesmentioning
confidence: 99%